Diagnostic Accuracy of Doppler Ultrasound on Portal Vein Flow Velocity (PVFV) for Esophageal Varices (EV) in Cirrhotic Patients Using Esophagogastroduodenoscopy as Gold Standard - Kumari, Reeaa; Mugheri, Ali Hyder; Kumar, Radhika Suresh; Saperna, . (Biological and Clinical Sciences Research Journal, 2025)
Esophageal varices are a frequent and potentially life-threatening complication of liver cirrhosis. Esophagogastroduodenoscopy (EGD) is the reference standard for diagnosis, but its invasive nature limits its routine use for screening. Doppler ultrasound assessment of portal vein flow velocity (PVFV) may offer a non-invasive alternative for identifying cirrhotic patients at risk of esophageal varices. Objective: The purpose of this study is to determine the diagnostic accuracy of Doppler ultrasound on Portal Vein Flow Velocity for Esophageal Varices (EV) in Cirrhotic patients, taking Esophagogastroduodenoscopy as the gold standard. Methods: After obtaining ethical approval from the institutional review board, this cross-sectional study was conducted at the Department of Gastroenterology, Shaheed Mohtarma Benazir Bhutto Medical University, Larkana, from 25 February 2025 to 25 July 2025. Through non-probability consecutive sampling, 111 patients aged 18-80 years, both genders, suspected patients of esophageal varices with a diagnosis of liver cirrhosis were included in the present study. Results: The diagnostic performance of Doppler ultrasound for detecting esophageal varices was evaluated using a 2×2 contingency table. Among 65 Doppler-positive patients, 50 were true positives (confirmed on EGD), and 15 were false positives. Out of 46 Doppler-negative patients, 14 were false negatives, and 32 were true negatives. Based on this, the sensitivity of Doppler ultrasound was calculated to be 78.12%, with a specificity of 68.09%. The positive predictive value (PPV) was 76.92%, the negative predictive value (NPV) was 69.57%, and the overall diagnostic accuracy was 73.87%. Conclusion: Doppler-based PVFV measurements generally agree with PVFV screening; the lower measured sensitivity and specificity indicate that training standards and cutoff values are needed for non-invasive EV screening.